Investigation on the optical and electrical properties of undoped and Sb-doped SnO2 nanowires obtained by the VLS method - Costa, I. M. [UNESP]; Cunha, T. R.; Cichetto, L.; Zaghete, M. A. [UNESP]; Chiquito, A. J. (Elsevier, 2021)
In this work, we report the effects of Sb doping on the optical and electrical properties of the SnO2 nanowires obtained by the vapor-liquid-solid (VLS) method. The absorption edges were found to be 3.30 eV and 3.66 eV for undoped SnO2 and Sb-doped SnO2 (ATO) nanowires, respectively. The energy shift was related to the Burstein-Moss effect taking place in the doped nanowires. We studied the ATO optical bandgap (ΔE = 0.36 eV) shift as a function of carrier concentration. The incorporation of Sb caused the resistivity to decrease three orders of magnitude for single-nanowire ATO devices. In addition, it was found that undoped SnO2 nanowires exhibit semiconductor characteristics while a metal-insulator transition (MIT), around 170 K, was observed in the ATO nanowires.
Keywords: ATO; Burstein-Moss shift; Metal-insulator transition; Nanowires; Single-nanowire device; Tin dioxide